The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.tecto.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional gravity and magnetic modelling of the Irish sector of the NE Atlantic margin

Abstract: A new 3D lithospheric model has been constructed using high-resolution gravity data from the Irish National Seabed Survey. The sedimentary component of the model incorporated density variations due to laterally varying overcompaction associated with Cenozoic denudation. After optimisation based on gravity inversion, regional crustal thickness variations were defined which are in reasonable agreement with the results of wide-angle seismic experiments. High crustal extension factors (β>5) characterise the deeper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 84 publications
(120 reference statements)
6
18
0
Order By: Relevance
“…The volcanic province is shown and highlighted with a yellow dotted line. Volcanic features in Rockall Basin are shown, based on the location of strong positive magnetic anomalies [after Kimbell et al , ], and those which appear to be conjugate to the CGVP are indicated by a dotted yellow line. The Barra Volcanic Ridges are shown, one of which aligns with the southern branch of the CGVP, along the trend indicated by the solid red line.…”
Section: Discussionmentioning
confidence: 99%
“…The volcanic province is shown and highlighted with a yellow dotted line. Volcanic features in Rockall Basin are shown, based on the location of strong positive magnetic anomalies [after Kimbell et al , ], and those which appear to be conjugate to the CGVP are indicated by a dotted yellow line. The Barra Volcanic Ridges are shown, one of which aligns with the southern branch of the CGVP, along the trend indicated by the solid red line.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, extension proceeded far enough in the failed rifts separating continental fragments from the interior that exhumed and serpentinized mantle directly underlies the basin sediments. Exhumed mantle is inferred from seismic and potential field studies for the Porcupine Basin (Kimbell et al, 2010), Phu Khanh Basin (Savva et al, 2013), and the Santos Basin (Zalán et al, 2011). Microcontinents, such as Jan Mayen and the Seychelles, are surrounded by oceanic crust.…”
Section: Continental Fragments and Microcontinents: General Settingmentioning
confidence: 99%
“…However, it appears likely that these lavas are underlain by Mesozoic rifts that contain rocks with relatively high velocities, because of either overcompaction or a high concentration of sills. Magnetic anomalies over the Hatton Basin suggest substantial volumes of magmatic rocks (Kimbell et al 2010).…”
mentioning
confidence: 99%